The Relationship Between Peer Interaction and Early Childhood Social Behavior in Jorong Kuranji Kabupaten Lima Puluh Kota - Erawati, Silfia; Ismaniar, Ismaniar (Universitas Negeri Padang, 2025)
The background of this study is based on the low social behavior of early childhood children found in Jorong Kuranji, Lima Puluh Kota Regency. The low social behavior of early childhood children is thought to be related to the lack of interaction between children and their peers. This study aims to: 1) describe the social interaction with peers of early childhood children in Jorong Kuranji, Lima Puluh Kota Regency, 2) describe the social behavior of early childhood children in Jorong Kuranji, Lima Puluh Kota Regency, 3) see the relationship between peer interaction and social behavior of early childhood children in Jorong Kuranji, Lima Puluh Kota Regency. This study uses a correlational approach with a correlational type. The population in this study consisted of 63 mothers who have children aged 4-5 years with a total sample of 44. The sample in this study used a simple random sampling technique. The instrument used to collect data was a questionnaire, while data analysis used percentage calculations and product moment methods to measure the relationship between variables. The results of the study show that: 1) Social interaction with peers of early childhood children in Jorong Kuranji, Lima Puluh Kota Regency is still low; 2) the social behavior of early childhood aged 4-5 years in Jorong Kuranji, Lima Puluh Kota Regency is still low; and 3) there is a significant relationship between peer interaction and the social behavior of early childhood aged 4-5 years in Jorong Kuranji, Lima Puluh Kota Regency.